Design of 5kV Ti/4H-SiC Schottky Barrier Diode with Low Power Dissipation - Jain, Neeraj (My University, 2008)
Silicon carbide (SiC) is semiconductor materials that replace Si material very quickly in the semiconductor industry due to its superior intrinsic properties. SiC material properties allow devices with higher voltage rating and higher operating temperatures compared to Si, which translates into smaller and less expensive components. Switches and rectifiers are the key components of power electronics. This thesis is focused on the design of high voltage 5kV Ti/4H-SiC Schottky barrier diode with uniform and linearly graded doping profile. In linearly graded doping profile, a expression is obtained for calculating the drift region width which is much less compare to the drift region width calculated by the uniform doping profile at the same effective level of doping concentration. So due to reduction of drift region width the effective value of on resistance decreases that means power dissipation across the device decreases. To serve as a basis of comparison between uniform and linearly graded doping profile, power dissipation calculation were performed. At a set forward current density of 100 A/cm2 and effective doping level ,the power dissipation improvements in linearly graded doping profile is 35.16 % higher as compare to the uniform doping profile and this improvements decreases with further increasing the effective doping level or increasing the gradient value.
Keywords: 5kV Ti/4H-SiC; Low Power Dissipation